Reinforced Concrete Structures : analysis and design - Fanella, David A. (New York : McGraw-Hill Education, 2011)
Photographs show office and bank buildings, hospitals, colleges and schools, homes and apartments, hotels and restaurants, factories, shrines and temples, mainly of Western design.
Includes bibliographical references and index.
Keywords: Concrete structures